Sequence analysis and structure-function correlations of murine q, k, u, s, and f haplotype I-A beta cDNA clones. - Estess, P (1986)
I-A beta-chain cDNA clones from mice of the q, k, u, s, and f haplotypes have been isolated and sequenced. Nucleotide sequence comparisons among these five A beta chains show considerable allelic variation in the region encoding the first external (beta 1) domain of the mature A beta protein. The beta 1 domain variability is clustered into three discrete regions, two of which divide the A beta chains into subgroups, suggesting an evolutionary history for the separation of alleles in inbred strains of mice. The amino acid sequences of these five chains are compared to each other and to previously published I-A beta chains. Correlations are made between the primary structural differences and the serologic and immune response characteristics mapping to the I-A subregion.